Test-retest reliability of electromyographic variables of masseter and temporal muscles in patients with cerebral palsy - Giannasi, Lilian Chrystiane [UNESP]; Matsui, Miriam Yumi [UNESP]; Politti, Fabiano; Batista, Sandra Regina F. [UNESP]; Caldas, Bruna F. [UNESP]; Amorim, Jose Benedito O. [UNESP]; Franco de Oliveira, Luis Vicente; Oliveira, Claudia Santos; Gomes, Monica Fernandes [UNESP] (Elsevier B.V., 2014)
Introduction: The aim of this study was to evaluate the reliability of surface electromyography of the masticatory muscles in patients with cerebral palsy.Methods: Surface electromyography was performed over the masseter and temporal muscles in 15 patients with cerebral palsy with the mandible at rest and during maximum clenching effort in two sessions. The data were analyzed using the root mean square amplitude, mean frequency, median frequency, zero crossings and approximate entropy.Results: In the within-day evaluations, intraclass correlation coefficients were higher (0.80-0.98) for the all electromyography variables and muscles during maximum clenching effort. In the resting position, the coefficients revealed good to excellent reliability (0.61-0.95) for root mean square, mean frequency, median frequency and zero crossings and fair to good reliability (0.53-0.74) for approximate entropy. In the between-day evaluations, the coefficients revealed good to excellent reliability (0.60-0.86) for mean frequency, median frequency, zero crossings and approximate entropy. In the resting position, the coefficients revealed poor to fair reliability (0.23-0.57) for all electromyography variables studied. The root mean square had the highest standard errors during maximum clenching effort (2.37-5.91) and at rest (1.47-6.86).Conclusion: Mean frequency, median frequency and approximate entropy are the most reliable variables of surface electromyography signals of the masseter and temporal muscles during maximum clenching effort in individuals with cerebral palsy. These measures can be used to evaluate the function and behaviour of the masticatory muscles in this population following oral rehabilitation and surgical oral procedures as well as for the study the physiology of these muscles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cerebral palsy; Electromyography; Masticatory muscles; Reliability